Mula saysay at salaysay o paano dapat isálin ang creative non-fiction? - Almario, Virgilio S. (2021)
Access online through this link: https://journals.upd.edu.ph/index.php/Lirip/article/view/8822/7780
Keywords: Creative writing; Nonfiction; Translating and interpreting